Pediatric airway compression in aortic arch malformations: a multidisciplinary approach - Petreschi, Francesca; Coretti, Antonella; Porcaro, Federica; Toscano, Alessandra; Campanale, Cosimo Marco; Trozzi, Marilena; Secinaro, Aurelio; Allegorico, Annalisa; Cutrera, Renato; Carotti, Adriano (Frontiers in Pediatrics, 2023)
Background: aortic arch malformations (AAMs) should be suspected in the presence of persistent respiratory symptoms despite medical treatment or feeding problems in paediatric age.Aim: we report a descriptive cohort of patients with AAMs and the local management protocol applied.Methods: 59 patients with AAM were retrospectively reviewed. Three groups were identified: double aortic arch (DAA), group 1; complete vascular ring (non-DAA), group 2; anomalous origin of the innominate artery (IA), group 3.Results: prenatal diagnosis was available for 62.7% of patients. 49.2% of children were symptomatic. There was a significantly different prevalence of respiratory symptoms within the three groups: 73.7% in group 1, 24.2% in group 2 and 100% in group 3 (p-value: < 0.001). Surgery was considered in the presence of symptoms, in patients with DAA, and in those with reduction of the tracheal section area greater than 50%. 52.5% of patients underwent surgical repair (median age 6 months). The median follow-up interval was 21.9 months. Respiratory symptoms improved in most symptomatic patients.Conclusions: no specific protocols are available for the management of patients with AAMs.Conservative treatment seems to be reasonable for asymptomatic patients or those with airway stenosis less than 50%. A close follow-up is necessary to identify early patients who become symptomatic.